Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 8 - Polynomials and Factoring - 8-4 Multiplying Special Cases - Practice and Problem-Solving Exercises - Page 496: 37



Work Step by Step

To simplify the product $(2a+b)^{2}$ we'll apply the rule that states that $(x+y)^{2}$=$x^{2}$+2xy+$y^{2}$ and set x=2a and y=b Therefore, $(2a+b)^{2}$ =$(2a)^{2}$+2(2a)(b)+$b^{2}$ =$4a^{2}$+4ab+$b^{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.